Analisis Fatwa-Fatwa MUI Tentang Nikah di Bawah Tangan - R, Riska; Shuhufi, Muhammad; Amin, Abd Rauf Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In this research, the researcher is interested in examining the rights of women and children born from underhanded marriages and what the MUI fatwa regarding underhanded marriages is. The author uses normative legal research methodology and a fiqh approach. The author concludes that private marriages have many negative impacts, especially for women and children born from private marriages, there is no legal protection for the rights of wives and children because hand-held marriages are not registered by the State. In this case, the author agrees with the MUI to require marriages to be registered in official government institutions. The official institution in question is the Ministry of Religion through the Director General of Islamic Community Guidance, then through the Regional Office of the Ministry of Religion, Province, then the Ministry of Religion, Regency, City, then distributed to the KUA in each District throughout Indonesia. takes priority over attracting benefits and the rule of sad al-Zari'ah (closing the path of damage)